Strategi Surat Kabar Radar Depok Dalam Mengantisipasi Media Online - Sitiana Nurhasanah; Jufri Alkatiri (Fakultas Ilmu Komunikasi Universitas Pancasila, 2019)
The purpose of this study is to determine the efforts of the Depok Radar newspaper that can maintain its existence and anticipate competition in the media industry, especially in the current online media era. The concept studies used are mass media strategies and mass media (newspapers, online media). The research paradigm is post-positivist, the research approach is qualitative. The unit of analysis is individuals namely managing editor Radar Depok, and senior journalists. Data collection techniques using in-depth interviews, non-participant observation and documentation, as well as the validity of the data using source triangulation techniques. The results of this study indicate that for Radar Depok online media is not a big threat because according to him Radar Depok already has its own market. The strategy at Radar Depok is to do visual innovation, load the latest rubrics with specific moments, and have online media. For Radar Depok, the strategy efforts undertaken are aimed at maintaining its customers so as not to decrease, and the strategies that have been carried out are all expected to attract the attention of new readers of the Radar Depok newspaper.